2022
DOI: 10.1093/jisesa/ieac001
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Viral Transgenerational Immune Priming in Honey Bees (Hymenoptera: Apidae)

Abstract: Transgenerational immune priming is the process of increased resistance to infection in offspring due to parental pathogen exposure. Honey bees (Apis mellifera L. (Hymenoptera: Apidae)) are hosts to multiple pathogens, and this complex immune function could help protect against overwhelming infection. Honey bees have demonstrated transgenerational immune priming for the bacterial pathogen Paenibacillus larvae; however, evidence for viral transgenerational immune priming is lacking across insects in general. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…A difference in the expression of TGIP according to exposure route was also observed when honey bee queens were orally exposed to deformed wing virus or when injected with this virus [ 26 ]. This study suggested an interaction between the host genetics or epigenetics factors and the route of exposure in determining TGIP expression [ 26 ]. Such interactions could explain why other studies failed to orally induce TGIP in honey bee against the same inactivated virus [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A difference in the expression of TGIP according to exposure route was also observed when honey bee queens were orally exposed to deformed wing virus or when injected with this virus [ 26 ]. This study suggested an interaction between the host genetics or epigenetics factors and the route of exposure in determining TGIP expression [ 26 ]. Such interactions could explain why other studies failed to orally induce TGIP in honey bee against the same inactivated virus [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGIP expression thus may depend on the pathogen used for priming, host genetics, epigenetic factors or methodological issues such as the exposure procedure (e.g. [ 21 , 26 ]). Designing experiments to test the role of these factors and standardising experimental approaches are desirable to improve our understanding of TGIP mechanisms and their triggers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ‘suppressed in ovo viral infection’ (SOV) trait described by De Graaf et al [ 65 ] may result from transgenerational immune priming against DWV and may prevent its vertical transmission. However, the effects of queens’ DWV infection history on transgenerational immune priming still seems limited [ 66 ] and depended on multiple factors, including viral infection routes [ 67 ].…”
Section: Honey Bee Antiviral Immunitymentioning
confidence: 99%